Chronic bronchitis in textile workers. Issue 1 (January 1997) - Niven, R M; Fletcher, A M; Pickering, C A; Fishwick, D; Warburton, C J; Simpson, J C; Francis, H; Oldham, L A
Abstract : BACKGROUND: Exposure to cotton is known to produce a specific occupational disease known as byssinosis. A large population of textile workers was investigated to determine whether such exposure was also associated with chronic bronchitis once other possible aetiological factors had been accounted for. METHODS: A total of 2991 workers were investigated for the presence of symptoms compatible with chronic bronchitis. An MRC adapted respiratory questionnaire and MRC definition of chronic bronchitis were used for diagnostic labelling. Current and lifetime exposure to dust was estimated by personal and work area sampling, and the use of records of retrospective dust levels previously measured over the preceding 10 years. Airborne endotoxin exposure was measured using a quantitative turbidometric assay. Lung function tests were performed to measure forced expiratory volume in one second (FEV1) and forced vital capacity (FVC). A control group of workers exposed to man-made fibre textiles was identified. The comparative prevalence of chronic bronchitis in the two populations was assessed, allowing for sex, age, smoking habit, and ethnic origin. Two case referent studies were also performed; cases of chronic bronchitis were separately matched with controls from the cotton and control populations to determine the effect of the symptomatic state on lung function. RESULTS: After controlling for smoking (pack years), workers in a cotton environment were significantly more likely to suffer from chronic bronchitis and this was most marked in workers over 45 years of age (odds ratio 2.51 (CI 1.3 to 4.9); p < 0.01). Regression analysis of all possible influencing parameters showed that cumulative exposure to cotton dust was significantly associated with chronic bronchitis after the effects of age, sex, smoking, and ethnic group were accounted for (p < 0.0005). In the intra-cotton population case control study a diagnosis of chronic bronchitis was associated with a small decrement in lung function compared with controls: percentage predicted FEV1 in cases 81.4% (95% CI 78.3 to 84.6), controls 86.7% (84.9 to 88.5); FVC in cases 89.9% (95% CI 87.0 to 92.9), controls 94.6% (92.8 to 96.4). After controlling for cumulative past exposure and pack years of smoking the effect of the diagnostic state remained significant for both FEV1 (p < 0.01) and FVC (p < 0.05). CONCLUSIONS: Chronic bronchitis is more prevalent in cotton workers than in those working with man-made fibre and exposure is additive to the effect of smoking. The diagnosis of chronic bronchitis is associated with a small but significant decrement in lung function.